Research on the Controversy and Optimization Path of Rent Pricing Mechanism for Public Rental Housing: A Policy Analysis based on the Background of Concentrated Market Entry in Multiple Regions in 2025 - Lu, Yuzheng (International Journal of Social Sciences and Public Administration, 2026)
With the continuous advancement of urbanization in China, the housing pressure on new urban residents and young people has become prominent. The supply of public rental housing has entered a concentrated phase, and the rental pricing mechanism has sparked debates on fairness and sustainability. This paper focuses on the core issue: how to ensure the affordability of tenants while achieving sustainable operation of the project and addressing the conflicts of interests among multiple stakeholders. By using the methods of literature analysis and policy text comparison, and combining social justice, welfare pluralism and ecosystem theory to construct a three-dimensional analytical framework, this paper analyzes the structural contradictions in the current pricing mechanism. The research finds that rental governance needs to go beyond the administrative price limit thinking, establish a dynamic model of "benchmark rent + floating coefficient", promote the collaborative governance of the government, market, society and tenants, and introduce social workers to participate in demand assessment, rights advocacy and community mediation to enhance the inclusiveness and resilience of the system. The limitation lies in the lack of support from field interview data. In the future, qualitative research can be deepened by combining the practice of front-line social workers.